N-Formyl Peptide Receptors Induce Radical Oxygen Production in Fibroblasts Derived From Systemic Sclerosis by Interacting With a Cleaved Form of Urokinase Receptor - Napolitano, Filomena; Rossi, Francesca Wanda; Pesapane, Ada; Varricchio, Silvia; Ilardi, Gennaro; Mascolo, Massimo; Staibano, Stefania; Lavecchia, Antonio; Ragno, Pia; Selleri, Carmine; Marone, Gianni; Matucci-Cerinic, Marco; et al. (Frontiers in Immunology, 2018)
Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by fibrosis, alteration in the microvasculature and immunologic abnormalities. It has been hypothesized that an abnormal redox state could regulate the persistent fibrotic phenotype in SSc patients. N-Formyl peptide (fMLF) receptors (FPRs) are chemotactic receptors overexpressed in fibroblasts derived from SSc patients. In this study, we demonstrated that stimulation of FPRs promotes the generation of reactive oxygen species (ROS) in skin fibroblasts. In fibroblast cells, ROS production was due to FPRs interaction with the urokinase receptor (uPAR) and to 1 integrin engagement. FPRs cross-talk with uPAR and integrins led to Rac1 and ERKs activation. FPRs stimulation increased gp91phox and p67phox expression as well as the direct interaction between GTP-Rac1 and p67phox, thus promoting assembly and activation of the NADPH oxidase complex. FPRs functions occur through interaction with a specific domain of uPAR (residues 88SRSRY92) that can be exposed on the cell membrane by protease-mediated receptor cleavage. Immunohistochemistry analysis with a specific anti-SRSRY antibody, showed increased expression of uPAR in a cleaved form which exposes the SRSRY sequence at its N-terminus (DIIDIII-uPAR88–92) in skin biopsies from SSc patients. As expected by the increased expression of both FPRs and DII-DIII-uPAR88-92, fibroblasts derived from SSc patients showed a significantly increase in ROS generation both at a basal level than after FPRs stimulation, as compared to fibroblasts from normal subjects. C37, a small molecule blocking the interaction between FPRs and uPAR, and selumetinib, a clinically approved MAPKK/ERK inhibitor, significantly inhibited FPRs-mediated ROS production in fibroblasts derived from SSc patients. Thus, FPRs, through the interaction with the uPA/uPAR system, can induce ROS generation in fibroblasts by activating the NADPH oxidase, playing a role in the alteration of the redox state observed in SSc.